Intermediate Dutch [ a grammar and workbook - Oosterhoff, Jenneke A. (Grammar workbook series, 2009)
Suitable for learners who have achieved a basic proficiency and wish to refine their knowledge of grammatical structures, this book along with its companion volume "Basic Dutch", provides summaries of the essential points of Dutch grammar as well as opportunities to practice using the structures of the language